EKSISTENSI RELASIONAL SEKOLAH KATOLIK DAN DEPARTEMEN AGAMA SEBAGAI BENTUK KESATUAN TOLERANSI (Perwujudan Relasional Gereja dan Negara dalam Terang KHK) - Ambrosius Gerin Nugroho; Yohanes Endi (Lembaga Penelitian STKIP Widya Yuwana, 2022)
Relationships are the basis for establishing unity for related parties. The existence of Catholic Schools and State Departments is a sign and means of relation between Church and State. Both have their own duties and characteristics. Catholic schools are a means for the Church to grow in faith and education. Meanwhile, the Ministry of Religion is a means for the State to prosper as well as a forum for the existence of religious life. Catholic schools and the Ministry of Religion have a relationship that needs each other. The presence of a Catholic School which is also the presence of the Church requires a legal certainty in the form of a law that is accommodated by the State through the Ministry of Religion. The Ministry of Religion exists as a legal entity for the Church. The form of institutional relations between Catholic Schools and the Ministry of Religion is also established in the form of welfare relations in terms of completeness and providers of facilities and infrastructure. Catholic schools provide a form of relationship in the form of quality education and the birth of good people for the growth of faith and state life as well as offering educational facilities within a country. The Ministry of Religion provides a form of financial relationship and legal legality for Catholic schools. This is further clarified through Church law (KHK) which has specific points or themes that discuss the relationship between the Church and the State.